Becoming an Artist: the work of art beyond itself. An interview with Túlio Pinto - Caldas, Felipe Bernardes; Pinto, Túlio (PORTO ARTE: Revista de Artes Visuais, 2018)
The concern about how art and artists converse with production systems is not recent. It dates back at least to the 19th century. That interest gave rise to many arguments as well as functional attributions for the roles played by art and artists. How do artists converse with, share or challenge today’s capitalist production system, which would be centered on information, immateriality and the fusion of work and life? This interview with Túlio Pinto provides a reflective platform to think about what it means to work with art within a dialogue between the local and the global, the systems, the markets and the circuits in which contemporary art and its agents are placed and which they cross.